Self-Assembly Protein Superstructures as a Powerful Chemodynamic Therapy Nanoagent for Glioblastoma Treatment - Zheng, Tao; Wang, Wentao; Ashley, Jon; Zhang, Ming; Feng, Xiaotong; Shen, Jian; Sun, Yi (Nano-Micro Letters, 2020)
Glioblastoma (GBM) remains a formidable challenge in oncology. Chemodynamic therapy (CDT) that triggers tumor cell death by reactive oxygen species (ROS) could open up a new door for GBM treatment. Herein, we report a novel CDT nanoagent. Hemoglobin (Hb) and glucose oxidase (GOx) were employed as powerful CDT catalysts. Instead of encapsulating the proteins in drug delivery nanocarriers, we formulate multimeric superstructures as self-delivery entities by crosslinking techniques. Red blood cell (RBC) membranes are camouflaged on the protein superstructures to promote the delivery across blood–brain barrier. The as-prepared RBC@Hb@GOx nanoparticles (NPs) offer superior biocompatibility, simplified structure, and high accumulation at the tumor site. We successfully demonstrated that the NPs could efficiently produce toxic ROS to kill U87MG cancer cells in vitro and inhibit the growth of GBM tumor in vivo, suggesting that the new CDT nanoagent holds great promise for treating GBM. Highlights: 1 A new type of protein nanostructure as a chemodynamic therapy nanoagent was fabricated via proper assembling and crosslinking techniques. 2 The as-fabricated nanostructures could cross the blood–brain barrier, possessing excellent long circulating times and accumulation properties at the tumor site. 3 The RBC@Hb@GOx NPs can be regarded as ‘pure particles of drugs,’ which can produce toxic reactive oxygen species to inhibit the growth of orthotopic brain tumor. <figure> <picture><source srcset="//media.springernature.com/lw685/springer-static/image/art%3A10.1007%2Fs40820-020-00490-6/MediaObjects/40820_2020_490_Figa_HTML.png?as=webp" type="image/webp"></picture> </figure>